E-Servqual Analysis of Satisfaction and Loyalty on Tokopedia Consumers in Riau Province - frinov feldiko ibhar (Universitas Airlangga, 2022)
AbstractThe competitive e-commerce competition and the many alternatives make consumers selective in choosing the marketplace. E-servqual provided by e-commerce encourages consumers to make transactions which ultimately creates customer satisfaction and loyalty. This study examines the effect of E-servqual dimensions, namely efficiency, fulfillment, system availability, and privacy on satisfaction and loyalty consumers. The population in this study were Tokopedia consumers in Riau Province. The sampling technique used was purposive random sampling with a total sample of 100 respondents. They were collecting data using a questionnaire with a Likert scale. Data were analyzed using SEM (Structural Equation Modeling) analysis. The results partially showed an effect of efficiency, fulfillment, system availability, and privacy on satisfaction. Besides, there was also the influence of Efficiency, Fulfillment, system availability, and confidentiality on Loyalty through Satisfaction as a mediation. The higher consumer satisfaction level so that the higher consumer loyalty on Tokopedia.Keywords: E-servqual, E-commerce, Satisfaction and Loyalty